2014
DOI: 10.5001/omj.2014.110
|View full text |Cite
|
Sign up to set email alerts
|

What do Omani Women know about Breast Cancer Symptoms?

Abstract: The study revealed that there was lack of awareness and knowledge on breast cancer symptoms among Omani women. Breast cancer awareness and early detection through regular breast screening is important to reduce the mortality and morbidity of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 14 publications
1
36
1
Order By: Relevance
“…27 Other studies indicate that the women had a fair level of knowledge about breast cancer and BSE. [27][28][29][30][31][32][33] Knowledge is the result of to know of something and this happens after someone did sensing to a particular object. Knowledge occurs through the human senses of sight, taste and touch sensing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…27 Other studies indicate that the women had a fair level of knowledge about breast cancer and BSE. [27][28][29][30][31][32][33] Knowledge is the result of to know of something and this happens after someone did sensing to a particular object. Knowledge occurs through the human senses of sight, taste and touch sensing.…”
Section: Discussionmentioning
confidence: 99%
“…29 Several other factors were significantly associated with BSE knowledge and it practice are age and family history of breast cancer. 27 Research carried by Lakshmi et al 31 in Omani women found a significant association between family history of breast self-examination knowledge and practice. The awareness and practice of BSE was more frequent in the age group of 21-20 years.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…The current study is essential given the fact that breast cancer is the most common cancer among women in Oman (Renganathan et al, 2014). This study was funded by His Majesty the Sultan's Strategic Research Fund, with the aim of obtaining baseline information on the current status of breast cancer awareness among women in seven Omani governorates, with an ultimate goal of defining strategies that may be implemented to increase awareness of breast cancer and increase screening rates.…”
Section: Introductionmentioning
confidence: 99%